2019
DOI: 10.1519/jsc.0000000000003447
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory Responses to Endurance Exercise Over the Menstrual Cycle and With Oral Contraceptive Use

Abstract: Female steroid hormone fluctuations during the menstrual cycle and exogenous hormones from oral contraceptives may have potential effects on exercise performance. The aim of this study was to investigate the effects of these fluctuations on cardiorespiratory responses during steady-state exercise in women. Twenty-three healthy endurance-trained women performed 40 minutes of running at 75% of their maximal aerobic speed during different phases of the menstrual cycle (n 5 15; early follicular phase, midfollicula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
29
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 38 publications
10
29
2
1
Order By: Relevance
“…Concretely, HR showed lower values in the EFP compared to the LFP. Likewise, a recent research conducted with endurance trained females reported higher values of HR during the MLP compared to the mid-follicular phase [10]. This study also reported increments in body basal temperature during this phase and, as aforementioned, it may be accompanied by an increase in HR [3,30] and Ve [6,22,26]..…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Concretely, HR showed lower values in the EFP compared to the LFP. Likewise, a recent research conducted with endurance trained females reported higher values of HR during the MLP compared to the mid-follicular phase [10]. This study also reported increments in body basal temperature during this phase and, as aforementioned, it may be accompanied by an increase in HR [3,30] and Ve [6,22,26]..…”
Section: Discussionsupporting
confidence: 78%
“…They suggested that the increase in cardiorespiratory strain due to high intensity exercise is greater than any possible increase caused by progesterone. Hence, progesterone effect on this physiological variable may be masked by the high intensity exercise [3,10,31]. Thus, discrepancies in results could be related with the intensity of the protocols.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the same day, after feeding and resting (a minimum of 2 h after feeding), participants performed a maximal ramp test on a computerized treadmill (H/P/COSMOS 3PW 4.0, H/P/Cosmos Sports & medical gmbh, Nussdorf-Traunstein, Germany) to determine each participant's peak oxygen consumption ( . VO 2peak ) [41]. The laboratory environmental conditions were 708.7 ± 4.9 mmHg, 22.8 ± 1.6 • C and 72.9 ± 6.6% of relative atmospheric humidity.…”
Section: Methodsmentioning
confidence: 99%